Modern art in detail 75 masterpieces - Hodge, Susie 1960- (Thames & Hudson Ltd, 2017)
Great works of art cannot be fully understood in a single encounter: to get the most out of modern art, it pays to revisit and reconsider, to reflect and to scrutinize in detail. It is also helpful to understand a work's context: what has gone before, what it may be reacting against or extending, how it embraces new technologies, and how it relates to contemporary thinking on such subjects as politics, sexuality, identity and the role of the artist.